Artemisinin exerts anti-inflammatory effects in osteoarthritis through the inhibition of TGF-β1 signaling - Zheng, Xifan; Yu, Bo; Song, Yuansong; Chen, Yeping; Li, Zeming; Yao, Jun (Frontiers in Immunology, 2026)
ObjectiveOsteoarthritis (OA) involves an inflammatory imbalance, yet key mediators and their interplay with potential therapeutics like artemisinin (ART) remain poorly understood. This study aimed to systematically investigate these relationships using Mendelian randomization and to decipher their functional interactions through cellular and molecular experiments, complemented by network pharmacology and molecular docking analyses.MethodsUsing the Mendelian randomization (MR) method, we integrated independent exposure–outcome genome-wide association study data to evaluate the causal association between inflammatory cytokines and OA. Chondrocytes were treated with IL-1β, TGF-β1 (5 μg/mL), and ART (4 μg/mL) for 24 hours. Cell proliferation was assessed using CCK-8 and EdU assays, and gene/protein expression was analyzed via RT-qPCR, Western blotting, and immunofluorescence staining. In parallel, network pharmacology was performed to identify putative ART targets related to OA and to characterize enriched pathways and hub genes through GO/KEGG enrichment and protein–protein interaction (PPI) analyses. Molecular docking was further conducted to evaluate the binding feasibility between ART and the catabolic mediator MMP-13.ResultsMR revealed a positive association between TGF-β1 and OA risk (OR = 1.0526, P = 0.0182). Functionally, ART significantly enhanced chondrocyte proliferation, whereas TGF-β1 inhibited it. ART downregulated IL-1β and MMP13 expression, while TGF-β1 upregulated them, indicating opposing effects in OA chondrocytes. Network pharmacology suggested that ART-related OA targets were enriched in inflammation-associated processes and signaling pathways (e.g., MAPK signaling), with PPI analysis highlighting inflammatory signaling hubs (e.g., JAK/STAT-related nodes). Consistently, molecular docking demonstrated favorable binding of ART within the MMP-13 active pocket, supporting the structural feasibility of an ART–MMP-13 interaction.ConclusionThis study demonstrates that TGF-β1 plays an important pathogenic role in OA, as supported by MR and in vitro evidence, while ART exhibits anti-inflammatory and anti-catabolic effects by counteracting TGF-β1–driven inflammatory responses. Network pharmacology and docking analyses further suggest multi-target pathway regulation and a potential interaction with MMP-13. ART may represent a viable therapeutic candidate for OA; however, further studies are required to validate direct targets and elucidate tissue-specific mechanisms.